2018
DOI: 10.1039/c8cc07530a
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic and asymmetric investigations of the Au-catalysed cross-coupling between aryldiazonium salts and arylboronic acids using (P,N) gold complexes

Abstract: Aryldiazonium salts and arylboronic acids were coupled via three different pathways from (P,N)–AuCl complexes, with enantiomeric excesses up to 26%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 66 publications
0
26
0
Order By: Relevance
“…Dual Au and photoredox catalyzedintramolecular( a) alkoxyarylation, [272] (b) amino-arylation, [273] and (c) ipso-arylation-cyclization [274] reactions of alkynes with aryl diazonium salts. [279] Insteado fa rylboronic acids, Patil et al utilized arylsilanes as the coupling partners for the diaryl-forming reactions. [275,276] Based on stoichiometric experiments, Fouquet et al have further investigated the mechanismsf or the cross-coupling of arylboronic acids with aryldiazonium salts and used the methodologies for enantioselective synthesis of biaryls.…”
Section: Dual Gold and Photoredox Catalysisf Or Cross-couplingr Eactionsmentioning
confidence: 99%
“…Dual Au and photoredox catalyzedintramolecular( a) alkoxyarylation, [272] (b) amino-arylation, [273] and (c) ipso-arylation-cyclization [274] reactions of alkynes with aryl diazonium salts. [279] Insteado fa rylboronic acids, Patil et al utilized arylsilanes as the coupling partners for the diaryl-forming reactions. [275,276] Based on stoichiometric experiments, Fouquet et al have further investigated the mechanismsf or the cross-coupling of arylboronic acids with aryldiazonium salts and used the methodologies for enantioselective synthesis of biaryls.…”
Section: Dual Gold and Photoredox Catalysisf Or Cross-couplingr Eactionsmentioning
confidence: 99%
“…In 2018, Hermange, Fouquet, and co-workers reported that biaryl products could be obtained in up to 26% ee using mononuclear gold complexes bearing chiral P,N-ligands (Scheme 27a). 48 The two-step stoichiometric cross-coupling method relies on an initial transmetalation with an arylboronic acid followed by coupling with an aryldiazonium salt under photoredox conditions. In 2019, Kramer and co-workers demonstrated that stoichiometric aryl-aryl homocoupling can be achieved with up to 91% ee by using binuclear gold complexes bearing C 2 -symmetric chiral ligands (Scheme 27b).…”
Section: Discussionmentioning
confidence: 99%
“…If the reaction is carried out in the absence of a light source, the N 2 ‐unit from the diazonium salt is retained and azobenzofurans are formed in moderate to high yields. Stoichiometric experiments demonstrate that these products are accessible from the same vinyl Au I intermediate and lead us to propose that the often suggested photochemical oxidative addition either occurs after the formation of a vinyl Au I species or may even not involve oxidation state changes.…”
Section: Methodsmentioning
confidence: 99%